Implementasi Program Pemberdayaan Usaha Mikro Kecil Menengah (Pada Dinas Koperasi Usaha Mikro Dan Perdagangan Kota Batu) - Pernandes Frans Putra (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2022)
AbstractIn starting a business, it is often constrained by the lack of capital, poor administrative ability and lack of experience on how to promote the products. Based on those empirical problems, it is necessary to empower an entrepreneur. Micro, Small and Medium Enterprises are business activities that are able to expand employment, increase income, encourage local economic growth, and realize the stability of the Batu Region. This study used a qualitative method and determined the respondents with a snowball sampling. The technique of collecting data was through interviews, observation, documentation. The data analysis technique involved reduction, presentation, and verification. The results of the study showed that the government has put experts in their respective fields, supported by human resources, nature and budget, implementation of empowerment, identified through facts or phenomena that occured in the field by means of communication, and coordination, as well as having an impact on the social economic environment. The supporting factors were the communication, the availability of empowerment consultants, budgets, and the Batu Employers Association Group. While the inhibiting factors were the competition, not having business licenses, weather changes and the lack ability of recording material presented by the resource person. Keywords: Empowerment Program, Micro, Small and Medium Enterprises